The effect of nacre extract on cord blood‐derived endothelial progenitor cells: A natural stimulus to promote angiogenesis?. Issue 7 (25th February 2019) - Willemin, Anne‐Sophie; Zhang, Ganggang; Velot, Emilie; Bianchi, Arnaud; Decot, Veronique; Rousseau, Marthe; Gillet, Pierre; Moby, Vanessa
Abstract: Angiogenesis is a critical parameter to consider for the development of tissue‐engineered bone substitutes. The challenge is to promote sufficient vascularization in the bone substitute to prevent cell death and to allow its efficient integration. The capacity of nacre extract to restore the osteogenic activity of osteoarthritis osteoblasts has already been demonstrated. However, their angiogenic potential on endothelial progenitor cells (EPCs) was not yet explored. Therefore, the current study aimed at investigating if nacreous molecules affect EPC behavior. The gene and protein expression levels of endothelial cell (EC)‐specific markers were determined in EPCs cultivated in presence of a nacre extract (ethanol soluble matrix [ESM] at two concentrations: 100 μg/mL and 200 μg/mL (respectively abbreviated ESM100 and ESM200)). Cell functionality was explored by proangiogenic factors production and i n vitro tube formation assay. ESM200 increased the expression of some EC‐specific genes. The in vitro tube formation assay demonstrated that ESM200 stimulated tubulogenesis affecting angiogenic parameters. We demonstrated that a stimulation with 200 μg/mL of ESM increased angiogenesis key elements. This in vitro study strongly highlights the proangiogenic effect of ESM. Due to its osteogenic properties, previously demonstrated, ESM could constitute the key element to develop an ideal prevascularized bone substitute. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2019.